Sens(a)ble Intermediality and Interesse: Towards an Ontology of the In-Between - Oosterling, Henk (Intermédialités / Intermediality, 2003)
In this article the specific quality of the “in-between” or “inter” within the notion of intermediality is explored. First the Gesamtkunstwerk and Foucault's “esthetics of existence” are analyzed in terms of intermediality. By tracing the historical roots of this notion the perspective for its actuality is widened. Next, a positioning of the “inter” in a mainly German discussion on intermediality is elaborated, criticizing hermeneutics and dialectics. Subsequently this discussion is related to a philosophical debate on the sublime and on mediation by French philosophers of difference as Derrida, Lyotard and Nancy. Finally the contours of an ontology of the “in-between” are redefined in terms of the Kantian and Heideggerian Inter-esse.